2022
DOI: 10.3390/ijms23020679
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced Magnetic Resonance Imaging for the Prediction of Monoclonal Antibody Tumor Disposition

Abstract: The prediction of monoclonal antibody (mAb) disposition within solid tumors for individual patients is difficult due to inter-patient variability in tumor physiology. Improved a priori prediction of mAb pharmacokinetics in tumors may facilitate the development of patient-specific dosing protocols and facilitate improved selection of patients for treatment with anti-cancer mAb. Here, we report the use of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), with tumor penetration of the contrast agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Instead, DCE-MRI or ICG with NIR are viable options to assess vascular permeability and passive transport. Bordeau et al showed recently that the addition of K trans to physiologically based pharmacokinetic modelling improved the accuracy of mAb tumour disposition in a mouse model [105]. At a minimum we hypothesise that assessment of the ICG signal from individual rectal tumours would provide thousands [93] or even hundreds of thousands [94].…”
Section: Beyond Cancer/not Cancer Labellingmentioning
confidence: 89%
See 1 more Smart Citation
“…Instead, DCE-MRI or ICG with NIR are viable options to assess vascular permeability and passive transport. Bordeau et al showed recently that the addition of K trans to physiologically based pharmacokinetic modelling improved the accuracy of mAb tumour disposition in a mouse model [105]. At a minimum we hypothesise that assessment of the ICG signal from individual rectal tumours would provide thousands [93] or even hundreds of thousands [94].…”
Section: Beyond Cancer/not Cancer Labellingmentioning
confidence: 89%
“…Pharmacokinetic model analysis has shown that monoclonal antibody (mAb) tumour disposition is influenced by passive transport processes such as capillary permeability [103,104]. These passive transport processes cannot be assessed on histopathological biopsies [105]. Instead, DCE-MRI or ICG with NIR are viable options to assess vascular permeability and passive transport.…”
Section: Beyond Cancer/not Cancer Labellingmentioning
confidence: 99%